Pengaruh Dosis Pupuk Majemuk NPK + Zn terhadap Pertumbuhan, Produksi, dan Serapan Zn Padi Sawah di Inceptisol, Kebumen - Latifah Arifiyatun; Azwar Maas; Sri Nuryani Hidayah Utami (Universitas Muhammadiyah Yogyakarta, 2016)
The study was conducted to identify the optimum Zn formula that could be added to dose 300 kg/ha NPK fertilizer with the additional 200 kg/ha urea, organic fertilizer 500 kg/ha and its implication on Zn nutrient uptake and paddy production. Generally, paddy cultivation practices applied macro-synthetic fertilizers without returning crop residues and organic materials as a soil conditioner as well as to provide micronutrients. In addition, the accumulation of P in the soil is pressing the availability of Zn, at neutral pH to alkaline Zn is not available and relatively mobile, when the soil is waterlogged Zn would be settled, and usually Zn is never be fertilized. Moreover, the land is intensively used for the manufacture of bricks and tiles indicate experiencing Zn depletion will cause symptoms on leaves of rice plants reduced toughness, pale green after 2-4 days later on flooded would be krotik and dried up. The research of fertilization innovation on micronutrients were conducted on July 2014 – January 2015 in Green House Agriculture Faculty, the University of Gajah Mada where the planting media of this research was Inceptisol which taken from Kebumen. The treatment were 10 treatments with a dose of NPK Plus Zn 0.25% Zn content ranges from 0% to 2% Zn repeated 3 times using a complete randomized design (CRD). The results showed that the land was given an additional 1.75% Zn has provided the highest Zn content of 0.16 mg/kg with a content of Trubus tissue's Zn 68,38 mg/kg. Whereas in the control treatment had the lowest score is 0.07 mg/kg with Zn content of trubus tissue was 47.85 mg/kg. Not seen an increase in yield due to the additional provision of 2% Zn to the dose of NPK fertilizer plus Zn were given, but the tendency dose of 1.75% Zn gives the highest production yield with and extrapolated enough to the total population reached 9.96 tons/ha while in control was only 3.45 tons/ha.